Analysis of defensive playing styles in the professional Chinese Football Super League - Ruan, L.; Ge, H.; Gómez, M.-A.; Shen, Y.; Gong, B.; Cui, Y. (Science and Medicine in Football, 2023)
Aim: Describing and measuring different team styles of play during matches is a key step towards a more predictive and prescriptive performance analysis. The current study aimed to identify and measure different defensive playing styles associated with technical-tactical and physical performance indicators in professional football via Principal Component Analysis (PCA). Methods: The sample comprised all 240 matches played in the Chinese Football Super League (CSL) during the 2018 season. Results: Seventeen key performance indicators (KPIs), 15 defense-related and 2 physical-related were identified from a total of 62 defensive performance indicators, which significantly differed between when teams lost and did not lose (p<0.05, ES=0.03-0.22). Then the PCA model based on 17 KPIs (Kaiser-Meyer-Olkin value being 0.81), outputted 8 factors representing 7 different styles of play (factor 6 and 8 represented one style) and explaining 83.01% of the total variance. Of all styles, defense close to own goal, including clearance, ball gain in the zone 1, deep completion and unsuccessful cross of the opponent, was the most dominant style (31.92% of the total variance). The champion of the league showed better scores in all styles of play, while the last ranked team got the highest score in defense close to the own goal style. Conclusion: The study indicated that a team`s defensive style could be defined by specific KPIs, and teams are suggested to attune their styles consciously rather than maintaining a consistent strategy so as to achieve better performance. Moreover, such categorization of defensive styles could be used during scouting and match preparation.